The association between statin use and age related maculopathy. Issue 9 (20th August 2003) - McGwin, G; Owsley, C; Curcio, C A; Crain, R J
Abstract : Aims: To evaluate the association between age related maculopathy (ARM) and statin use. Methods: A nested case-control study among patients at the Veterans Affairs Medical Center in Birmingham, Alabama, with newly diagnosed ARM (cases) between 1997 to 2001 were selected and age matched to non-ARM controls. Results: 550 incident cases of ARM were identified and matched to 5500 controls. Overall, cases were 70% (OR 0.30, 95% CI 0.21 to 0.45) less likely to have received and filled a statin prescription relative to the controls. This association was present among both current and past (OR 0.34, 95% CI 0.21 to 0.53 and OR 0.26, 95% CI 0.14 to 0.47, respectively) statin users. When considering use of statin and/or non-statin lipid lowering medications, a significant risk reduction was observed for statin only users (OR 0.30, 95% CI 0.20 to 0.45) and combined statin and non-statin users (OR 0.20, 95% CI 0.06 to 0.64); there was no significant association for non-statin only users (OR 0.47, 95% CI 0.20 to 1.13). Conclusions: The results of this study suggest that subjects with ARM were significantly less likely to have filled a statin prescription. Future clinical research initiatives should include a clinical trial to provide direct evidence of the effectiveness of statins in lowering the incidence and progression of ARM.